THE EFFECTIVENESS OF ISLAMIC FILM AS MEDIA TO TEACH LISTENING AT MA ARRAHMAN JOMBANG - Khudriyah; Nurkhamimi Zainuddin; Wisetrat Wilailak (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2024)
Listening comprehension is an active process in which the listener constructs meaning through using cues from contextual information and from existing knowledge, while relying upon numerous strategic resources to perform the task requirement, so it is very difficult to tech especially as foreign language, and needs appropriate media to teach it. This research is aimed to know whether or not Islamic film as media to teach listening effective. And what steps to teach listening using Islamic film as media. This research is mix method; the data was collected using test, questionnaire, interviews, and observation. The data then analyzed by paired sample t-test, the data had been obtained was clarified by analyzing the results of the questionnaire and in-depth interviews, and observation. The result show that there is significant difference students listening ability before and after giving film as media. As proved by the score of t account > t table using one-tailed, and degree of freedom 63 (19.516 > 1.68023, and the result of (P-Value) is also lower than alpha (0.000 < 0.05). The steps of teaching listening using Islamic film as media: First, the teacher was providing films in accordance with students' characteristic; the teacher then can skipped the one that was a bit pornographic. The next, the teacher determined time for listening subject, and created conducive atmosphere. The teacher then gave warming up to the students. After that the students were asked the teacher to watch film with subtitle. The next, the teacher asked students to note vocabulary at film that they didn’t understand the meaning, then looking the meaning on the dictionary or internet to know the meaning. The teacher then implement the film by asking students to watch film without using subtitle without being crowded. At the end of the lesson, the teacher asked some questions about the topic of the film, and evaluates them.